2022
DOI: 10.17219/dmp/145894
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical localization of posterior superior alveolar artery: A retrospective study by cone-beam computed tomography

Abstract: Background. Familiarity with the anatomy of the arteries in the sinus wall is essential to prevent the perforation of the sinus membrane and bleeding during dental implant surgery.Objectives. The aim of the study was to evaluate the anatomical position of the posterior superior alveolar artery (PSAA), using cone-beam computed tomography (CBCT). Material and methods.A total of 245 CBCT scans met the eligibility criteria for this cross-sectional study. The vertical distance from the lower border of the artery to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Both vessels can be damaged during the positioning of the miniscrew. This can lead to postoperative complications in the form of prolonged bleeding [ 49 , 50 , 51 ]. Jia et al [ 21 ] assessed the incidence of TADs penetration into the maxillary sinus and penetration depth influence on sinus tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Both vessels can be damaged during the positioning of the miniscrew. This can lead to postoperative complications in the form of prolonged bleeding [ 49 , 50 , 51 ]. Jia et al [ 21 ] assessed the incidence of TADs penetration into the maxillary sinus and penetration depth influence on sinus tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It was suspected to be the posterior superior alveolar artery [ 5 , 6 ]. Firm pressure was applied directly over the channel.…”
Section: Technical Notementioning
confidence: 99%
“…In the context of medical imaging, it has been observed that the utilization of cone beam computed tomography (CBCT) results in a notable reduction in the radiation dose experienced by the patient when compared to conventional computed tomography (CT) [13]. In recent years, there have been significant technological advances, resulting in the attainment of much higher levels of resolution in dental imaging [14].…”
Section: Introductionmentioning
confidence: 99%